Hubungan Pola Asuh Orang Tua dengan Tingkat Perkembangan Anak TK Usia 4-6 Tahun - Anjani, Ida Ayu Ketut; Sipahutar, Ida Erni; Yunianti Suntari Cakera, Ni Luh Putu (Jurnal Gema Keperawatan, 2024)
Developmental disorders are currently a global health problem. The state of increasing population every year shows that delays in child development will also continue to increase. The purpose of the research is to find out about parenting styles of parents with the level of child development. This type of research is quantitative which is correlational and the research design uses a cross sectional approach. The total sample was 127 people using the probability sampling method, namely the proportional stratified random sampling technique. The sample was determined based on inclusion criteria, namely parents and their children who attended the Pusat PAUD Werdhi Kumara and exclusion criteria, namely parents and children who were present but could not participate as respondents. Data collection used parenting style questionnaires and developmental pre-screening questionnaires. The results showed that the parenting style of the majority was democratic (61,4%), and the majority of children had appropriate development (85%). Test the hypothesis using chi square with asymp values. Sig (2-sided). The results of the chi square test of parenting style and child development showed a significance value of 0,467 or a p value 0,05, which means that there is no relationship between parenting style and child development. Based on a comparison of the calculated chi square value with the chi square table, the results obtained are 3,569 9,488. In conclusion, there is no relationship between parenting style and the level of development of kindergarten children aged 4-6 years at Kindergarten Pusat PAUD Werdhi Kumara Denpasar Selatan Year 2023. For future researchers, it is hoped that they can conduct further research on other factors that can provide the right stimulus at the developmental stage of preschool-aged children.